Empowering Students to Engage in the Design of COVID-19 Related Gamified Applications - Nicolaidou, Iolie (My University, 2022)
COVID-19 related games have recently been developed to combat misinformation and raise awareness of COVID19 protocols. COVID-19 related games or gamified apps were designed using top-down approaches (from company to players). The COVID-19 pandemic highlighted challenges in their uptake and usage. Strategies such as co-design may be leveraged to address these challenges, particularly for developing new technologies. This in-progress, exploratory mixedmethods study aimed to engage university students in designing gamified applications to address their needs amidst and post-pandemic. Its first step was to empower students to think of design ideas. The study's research questions were: What are students’ goals for designing pandemic-related gamified apps? To what extent do students make use of gamification techniques in their design? A convenience sample of 20 third/fourth-year undergraduates expressed their ideas individually, in an online class, at a time of university closures (May 2021). A second sample of 37 first-year undergraduates engaged in the same activity in a face-to-face class (December 2021). The data were analyzed using a qualitative data analysis software. Thematic analysis was used, data were coded, and themes and sub-themes emerged. Qualitative analysis of all 57 students’ responses revealed two main themes expressed by students as a goal for their app: a) increasing pandemic awareness and following hygiene protocols (24/57, 42.1%) and b) building resilience through different ways to cope with the pandemic, including physical exercise, social interaction, entertainment and education (31/57, 54.4%). Students maintained similar design goals for proposed apps despite increasingly less strict public-health measures from May to December 2021. The majority of students (52.6%, 30/57) used one to three gamification techniques, while 38.6% of them (22/57) did not use any. Third/fourth-year students used significantly more (t55=4.65, p=0.000) gamification techniques (M=2.35, SD=1.31) compared to first-year students (M=0.81, SD=1.13). The first stage of this study showed value in involving students in the design of interventions that targeted themselves and revealed the need for training students who lack a design background in identifying relevant gamification techniques. Future research will aim to materialize students’ suggested design ideas into design prototypes by involving them in the process through interdisciplinary collaborations.
Keywords: COVID-19 pandemic; app design; gamification; design for social impact; gamified apps